Relational Hubs for Collaborative Landscape Stewardship. Issue 5 (3rd May 2020) - Cockburn, Jessica; Cundill, Georgina; Shackleton, Sheona; Cele, Ayanda; Cornelius, Susanna Francina (Ancia); Koopman, Vaughan; le Roux, Jean-Pierre; McLeod, Nicky; Rouget, Mathieu; Schroder, Samantha; Van den Broeck, Dieter; Wright, Dale R.; et al.
Abstract: Landscape stewardship is considered an important place-based approach to addressing sustainability challenges. Working at landscape-level requires collaboration between diverse landscape stakeholders. In this study, we partnered with local stewardship practitioners across six cases in South Africa to investigate how they facilitate collaboration towards social-ecological sustainability outcomes. We found that practitioners facilitate collaboration among stakeholders by operating as relational hubs in the landscape. Through these hubs, they build new inter-personal relationships among stakeholders, creating social networks which enable stewardship practice. The hubs deepen human-nature relationships by creating enabling conditions for stewards to put stewardship ethics into action. Drawing on insights from these cases, we call for a relational approach to landscape stewardship which focuses on human-to-human and human-to-nature relationships. Moreover, we argue that landscape stewardship initiatives need to re-focus stewardship on stewards, recognizing them as key agents of change in addressing the conflict between agriculture and conservation inherent in many landscapes.